Cumulative Knee Joint Loads Associated with Interval Training - Reynolds, Victoria L (East Carolina University, 2016)
High-intensity interval training (HIIT) is defined as an exercise program involving cardiorespiratory training in repeated bouts of short duration at high intensities followed by short, recovery periods of lower intensity. The positive impact of HIIT on cardiorespiratory health is well established. However, the impact of HIIT on measures of musculoskeletal health and injury is still in need of research. The incidence of running-related injuries is very high and prohibits routine participation in physical fitness activities. At higher running speeds, people expend more energy, cover a greater distance with each step, and have shorter stance duration. It is possible that the decreased number of loading cycles associated with to HIIT for a given energy expenditure may reduce cumulative joint forces associated with overuse injuries, such as patellofemoral pain, that are commonly experienced during running. Therefore, the aim of this study was to compare knee joint contact forces between different HIIT protocols that are metabolically equivalent to prolonged running. Participants in this study ran on a treadmill at running speeds corresponding to their preferred running speed and at a speed corresponding to 95% VO2max in a motion capture lab as heart rate, energy expenditure, and 3D lower extremity kinematics and ground reaction forces were recorded. Data collected were used in a musculoskeletal model to calculate tibiofemoral joint and patellofemoral joint contact forces at each of the exercise intensities. Peak and cumulative knee joint contact forces and tibial stress measured during interval training and prolonged running were compared using separate repeated measures ANOVAs. These results may assist in the runners ability to continue to participate in their preferred exercise modality as well as to provide customized exercise prescription for prevention and alleviation of running-related injuries.
Keywords: high-intensity interval training; cumulative knee joint load; running-related injuries; lower extremity pain and running